Study on loss processes in solar cells - Abdurrhman, Ahmed B; Zakria, Fatima; Said, Hamed A. (Journal of Pure & Applied Sciences, 2021)
Determining heat sources for solar cells is essential to avoid energy loss, which in turn causes the efficiency of solar cells to decrease and therefore, the loss processes have a significant impact on solar conversion. This paper presents a study of intrinsic and exogenous losses in solar cells, identification of the resulting energy loss at different temperatures, and discusses the impact of exogenous and spectral reflectivity on solar cell performance. The results show an increase in thermal loss with an increase in temperature, which in turn leads to a decrease in the efficiency of solar cells. Also explained that the external radiate efficiency, spectral reflectance and operating temperature significantly affect the loss processes. The efficiency of the cell begins to decrease with the decrease of its external radiate efficiency.